Stratigraphy and eruption history of maars in the Clear Lake Volcanic Field, California - Ball, Jessica L. (Frontiers in Earth Science, 2022)
The Clear Lake Volcanic Field (CLVF) is the northernmost and youngest field in a chain of volcanic fields in the California Coast Range mountains. Effusive and explosive volcanic activity in the field has spanned at least 2.1 million years, with the youngest eruptions comprising a series of maar craters at the edges of, and within, Clear Lake itself. This work documents the first direct ages for many of these maar deposits and builds the stratigraphic basis for interpreting eruptive processes and dynamics of the young eruptions which produced them. Detailed stratigraphy has distinguished maar eruption products from pyroclastic deposits (monolithologic falls and flows, previously mapped together with maars as a single unit) and established a set of six eruption facies from maar deposit lithology, grain size parameters, and depositional structures. Radiocarbon dates from carbon films found on clasts at three outcrops have constrained several of these maar eruptions to ∼8,500–13,500 years BP, coinciding with eruptive periods previously estimated based on lake core tephrachronology. Part of this period also coincides with indigenous inhabitation (<12,000 years BP), which suggests that oral histories of Pomo and other local tribes may contain descriptions of volcanic phenomena experienced by local residents of the CLVF. Collaboration between volcanologists and indigenous historians may add a valuable human dimension to the youngest eruptions of the Clear Lake Volcanic Field, and help inform future volcanic hazard assessment.